Informative and cultural space as a factor of modern formation of nation in Ukraine - Krasiwski, Orest; Pidberezhnyk, Nadiia (Studia Europaea Gnesnensia, 2021)
The article analyzes the challenges to the Ukrainian nation-building and national security of Ukraine in the informative and cultural sphere at the present stage. Consequently, the author high- lights the problems of linguistic self-identification of Ukrainians, the functioning of the informative and cultural space as well as its impact on the formation of Ukrainian national consciousness are highlighted. Also, the paper determines the threats in the information sphere in the context of Rus- sia’s hybrid war against Ukraine and examines the formation of national consciousness through the system of national and patriotic education in Ukraine. The priorities of the state language policy, state policy in the information sphere and national-patriotic education in Ukraine at the present stage are defined in order to ensure the formation of the Ukrainian national consciousness and the Ukrainian civil nation, countering the challenges to the national security of Ukraine.